Effects of the COVID-19 pandemic on Czech citizens: how do depression and anxiety symptoms influence cognitive, behavioral, and emotional changes? - Hajkova, Dagmar; Sandora, Jan; Žídková, Radka; Malinakova, Klara; Novak, Lukas (Frontiers in Psychology, 2023)
Background: This study examined the impact of anxiety and depression symptoms during the first stage of the COVID-19 pandemic on the behavioral, cognitive, and emotional changes of the Czech population. Methods: The research sample (n=2363; 48.83 ±16.53years; 50.15% males), was obtained using an online survey. Depression and anxiety symptoms were measured using the Overall Depression Severity and Impairment Scale (ODSIS) and the Overall Anxiety Severity and Impairment Scale (OASIS) and associations were adjusted for age, gender, and economic status. Results: The results showed that increased symptoms of anxiety and depression were significantly linked to feelings of loneliness, helplessness, reduced quality of relationship with a partner, higher probabilities of alcohol abuse, food consumption, and contemplation of existential questions. Higher symptoms of anxiety were associated with feelings of being threatened. Higher symptoms of depression symptoms increased tobacco abuse. Conclusion: During the first stage of the COVID-19 pandemic, higher symptoms of anxiety and depression among Czech citizens were associated with behavioral, cognitive, and emotional changes.